Low-Intensity Exercise and Reduction of the Risk for Falls Among At-Risk Elders - Robert O. Morgan; B. A. Virnig; M. Duque; Elsayed Abdel-Moty; Carolee A. DeVito (2004)
Background. Among elderly persons, falls account for 87% of all fractures and are contributing factors in many nursing home admissions. This study evaluated the effect of an easily implemented, low-intensity exercise program on the incidence of falls and the time to first fall among a clinically defined population of elderly men and women.